Clinical features of coronavirus disease 2019 in Korean pediatric patients: a single-center retrospective study - Jeong, Ji Eun; Chung, Hai Lee; Kim, Young Hwan; Lee, Nawon; Kim, Younghyun; Jang, Yoon Young (Kosin Medical Journal (Online), 2024)
Background: To address the public’s fear of coronavirus disease 2019 (COVID-19), understanding the clinical features of the disease is essential. However, research on the clinical features of COVID-19, including illness duration and post-acute COVID-19, in Korean pediatric patients has been limited. Therefore, this study investigated the clinical features of COVID-19 based on the medical records of pediatric patients with a history of COVID-19 who visited a single center. Methods: In total, 311 patients were included in this study. The presence and duration of 19 symptoms were examined. Additionally, clinical features were investigated by dividing the patients into different age ranges. Patients aged 6 and above were further categorized according to the presence of asthma, while adolescent patients were divided into vaccinated and unvaccinated groups.Results: Fever and cough were the most common symptoms. The mean illness duration was 2–4 days. Only 3.5% of the patients were asymptomatic. Post-acute COVID-19 was observed in 13.2% of the patients. The incidence of most symptoms tended to increase with age. Post-acute COVID-19 was observed more frequently in patients with asthma than in those without asthma. Vaccinated patients experienced less fever, vomiting, and fatigue than unvaccinated patients.Conclusions: Our data suggest that most patients had mild disease lasting less than a week, and the clinical course may differ depending on the presence of asthma. The findings also indicate that vaccination may alleviate the symptoms of COVID-19 in breakthrough infections.